2005
DOI: 10.1093/jac/dki204
|View full text |Cite
|
Sign up to set email alerts
|

In vitro selection of resistance in Pseudomonas aeruginosa and Acinetobacter spp. by levofloxacin and ciprofloxacin alone and in combination with β-lactams and amikacin

Abstract: Use of combinations of fluoroquinolones with beta-lactams and amikacin reduces the risk for in vitro selection of resistant P. aeruginosa and Acinetobacter spp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 38 publications
0
19
0
1
Order By: Relevance
“…Recent studies also showed that the combination of a fluoroquinolone with a beta-lactam had in vitro and in vivo synergy against extended-spectrum betalactamase-producing Escherichia coli and P. aeruginosa isolates, respectively (8,22). This combination contributed less frequently than did monotherapy to in vitro selection for resistance in three different gram-negative bacilli (8,9).…”
mentioning
confidence: 99%
“…Recent studies also showed that the combination of a fluoroquinolone with a beta-lactam had in vitro and in vivo synergy against extended-spectrum betalactamase-producing Escherichia coli and P. aeruginosa isolates, respectively (8,22). This combination contributed less frequently than did monotherapy to in vitro selection for resistance in three different gram-negative bacilli (8,9).…”
mentioning
confidence: 99%
“…The highest synergy was seen in beta-lactam-fluoroquinolone and fluoroquinolone-AK combinations. 24 While in a study conducted in 2011, Tan et al 8 detected rate of synergy by CB method between polymyxin B-RF and TGC-RF as 19%, those between polymyxin B-TGC was 12%. The same rates obtained by TK methods were 56%, 19% and 44% respectively.…”
Section: Discussionmentioning
confidence: 98%
“…20,21,[25][26][27][28] We demonstrated that amikacin, gentamicin, or vancomycin can be delivered from the calcium sulfate dihydrate FAST pellets with effective dissolution and elution profiles. All FAST pellet formulations completely dissolved and eluted antibiotics in 12-24 h, whereas only 50% of the conventional pellet flakes had dissolved and 99.3% of antibiotic was released within this time frame.…”
Section: Discussionmentioning
confidence: 99%